1982
DOI: 10.1139/b82-066
|View full text |Cite
|
Sign up to set email alerts
|

Geographical variation in populations of Chenopodium album resistant and susceptible to atrazine. I. Between- and within-population variation in growth and response to atrazine

Abstract: WARWICK, S. I., and P. B. MARRIAGE. 1982. Geographical variation in populations of Chenopodium album resistant and susceptible to atrazine. I. Between-and within-population variation in growth and response to atrazine. Can. J. Bot. 60: 483-493. Between-and within-population variation in growth characteristics, isoenzyme patterns, and response to atrazine were studied in individuals from four atrazine-resistant (R) and four susceptible (S) populations of Chenopodium album L. collected from sites of contrasting … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

7
18
0

Year Published

1985
1985
2012
2012

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 29 publications
(25 citation statements)
references
References 13 publications
7
18
0
Order By: Relevance
“…, 2004). This is in accordance with other studies based on isozymes and AFLP markers, which reported lower variation for triazine‐ and triazinone‐resistant C. album populations compared with susceptible C. album populations (Warwick & Marriage, 1982; Al Mouemar & Gasquez, 1983; Aper et al. , 2010).…”
Section: Discussionsupporting
confidence: 93%
“…, 2004). This is in accordance with other studies based on isozymes and AFLP markers, which reported lower variation for triazine‐ and triazinone‐resistant C. album populations compared with susceptible C. album populations (Warwick & Marriage, 1982; Al Mouemar & Gasquez, 1983; Aper et al. , 2010).…”
Section: Discussionsupporting
confidence: 93%
“…Thus isoenzymes were used as an aid to design a progeny test to select ponderosa pine trees which produce seedlings with a superior ability to survive on degraded coal-mine spoils (Woods et al ., 1984), isoenzyme variation of C"henopodium album L. indicated a reduced variation in triazine herbicide resistant populations (Gasquez & Compoint, 1981 ;Warwick & Marriage, 1982) and similar results were obtained by Warwick & Black (1986) in Amaranthus retroflexus L. On the basis of esterase, endopeptidase, glutamate oxaloacetate transaminase and alcohol dehydrogenase isoenzyme variations, the present study was conducted to give a preliminary comparison of seven lots of date palm seedlings obtained from seven crosses using two male lines and seven cultivars as females . Good cultivars are generally characterized by their fruit quality and the level of resistance of Bayoud disease .…”
Section: Introductionsupporting
confidence: 64%
“…The main source of this variation in a géographie région in which résistance has not been detected previously is probably spontaneous gène mutation (Gasquez and Compoint 1981;Warwick and Marriage 1982). Rates of spontaneous gène mutation to herbicide résistance are unknown for any weed species, although a few estimâtes hâve been made in other plants.…”
Section: Mutation To Resistancementioning
confidence: 98%